Synthesis and Antimicrobial Studies of Some 3-Coumaryl-5-aryl Pyrazolines and Pyrazoles - THAKARE, N.R.; JAMODE, V.S. (Asian Journal of Chemistry, 2010)
Some 3-coumaryl-5-aryl pyrazolines (7a-f), (8a-f), (9af) and pyrazoles (10a-f) were synthesized and tested for antimicrobial activities against S. aureus, E. coli, Pr. mirabilis, Ps. aeruginosa. All these compounds were found effective against almost all micro-organisms.